2013
DOI: 10.1155/2013/726925
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Interleukin-2 (HD IL-2) Therapy Should Be Considered for Treatment of Patients with Melanoma Brain Metastases

Abstract: A retrospective review was performed on patients with stable melanoma brain metastases treated with HD IL-2 therapy (720,000 IU/kg per dose intravenously; 14 doses, 2 cycles per course, maximum 2 courses) from January 1999 to June 2011 at Saint Louis University. There were 5 men and 3 women; median age was 52.2 years (26.8–61.1 years). One patient started treatment with lung lesions only (after resection of melanoma brain disease) and experienced partial response. Seven patients had brain metastases at treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…In our study, all these cytokines are elevated in serum of animals treated with NIC combination, supporting increased cytotoxic activity of the immune system. Some of these cytokines have been used in anti-cancer treatment: IL-4 for GBM 36,37 IL-12 for breast cancer brain metastasis 38 , IL-2 for melanoma brain metastasis 39,40 , and IFN-α and IL-2 for renal cell carcinoma 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all these cytokines are elevated in serum of animals treated with NIC combination, supporting increased cytotoxic activity of the immune system. Some of these cytokines have been used in anti-cancer treatment: IL-4 for GBM 36,37 IL-12 for breast cancer brain metastasis 38 , IL-2 for melanoma brain metastasis 39,40 , and IFN-α and IL-2 for renal cell carcinoma 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Although case studies and small trials of HD IL-2 (n<10) in this population have recently suggested that it may be safe for patients with MBM, its efficacy in these patients has not been evaluated in a larger study. (Powell, Dudek 2009; Chu et al 2013) Other cytokines, including interferon alpha have also been used in melanoma, with limited success and marked toxicity (Kalaaji 2007). Some clinical studies have also evaluated granulocyte–macrophage colony-stimulating factor (GM-CSF) as a single agent or as adjuvant therapy with inconsistent results and unclear clinical benefit (Kaufman et al 2014).…”
Section: ) Treatment Options In Patients With Mbmmentioning
confidence: 99%
“…Only minor clinical benefit was observed [8]. Another small series of 8 patients reported progressive disease in all but 1 patient, pointing to an insufficient anti-tumor activity of single IL-2 treatment [9]. Because of the emergence of more advanced immunotherapeutics, cytokines have not been pursued extensively as therapeutic agents within the last few years.…”
Section: Cytokinesmentioning
confidence: 99%